1995
DOI: 10.1111/j.1528-1157.1995.tb02566.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic and Morphologic Characteristics of Granule Cell Circuitry in Human Epileptic Hippocampus

Abstract: Morphological and electrophysiological techniques were used to examine granule cells and their mossy fiber axons in nine surgically resected hippocampal specimens from temporal lobe epilepsy (TLE) patients. Timm histochemistry showed mossy fiber sprouting into the inner molecular layer (IML) of the dentate in a subset of tissue samples. In slices from five tissue samples, stimulus-induced bursting activity could be induced with a low concentration (2.5 microM) of bicuculline; bursts were sensitive to the N-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
129
0
5

Year Published

1996
1996
2003
2003

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 233 publications
(141 citation statements)
references
References 42 publications
7
129
0
5
Order By: Relevance
“…These data argue that infrapyramidal blade excitability may relate, or even depend, on the anatomic differences. Indeed, this possibility supports the hypothesis in the literature that mossy fiber sprouting increases dentate gyrus excitability, based on anatomic (Frotscher and Zimmer, 1983;Represa et al, 1993;Franck et al, 1995;Okazaki et al, 1995;Sutula et al, 1998;Wenzel et al, 2000) and physiological data (Tauck and Nadler, 1985;Sutula et al, 1992Sutula et al, , 1998Dudek et al, 1994;Pollard et al, 1996;Wuarin and Dudek, 1996;Patrylo and Dudek, 1998;Molnar and Nadler, 1999;Okazaki et al, 1999).…”
Section: Physiological Asymmetries and Their Relationship To Anatomicsupporting
confidence: 72%
“…These data argue that infrapyramidal blade excitability may relate, or even depend, on the anatomic differences. Indeed, this possibility supports the hypothesis in the literature that mossy fiber sprouting increases dentate gyrus excitability, based on anatomic (Frotscher and Zimmer, 1983;Represa et al, 1993;Franck et al, 1995;Okazaki et al, 1995;Sutula et al, 1998;Wenzel et al, 2000) and physiological data (Tauck and Nadler, 1985;Sutula et al, 1992Sutula et al, , 1998Dudek et al, 1994;Pollard et al, 1996;Wuarin and Dudek, 1996;Patrylo and Dudek, 1998;Molnar and Nadler, 1999;Okazaki et al, 1999).…”
Section: Physiological Asymmetries and Their Relationship To Anatomicsupporting
confidence: 72%
“…For light microscopy detection in mouse and monkey brains, a Timm's-staining protocol described by Franck et al (18) was adapted. Fixed hippocampal slices (1 mm) were immersed in 0.4% Na 2 S for 30 min, then fixed ϳ16 hr in 1% paraformaldehyde and 1.25% glutaraldehyde.…”
Section: Methodsmentioning
confidence: 99%
“…Targets for these sprouted terminals include both DGCs and inhibitory interneurons (21,22). Extracellular, intracellular, and optical recording studies have demonstrated that these sprouted MFs are functional, i.e., activation of these collaterals elicits excitatory responses in the dentate gyrus (21,(23)(24)(25).…”
Section: Mossy Fiber Sproutingmentioning
confidence: 99%
“…Targets for these sprouted terminals include both DGCs and inhibitory interneurons (21,22). Extracellular, intracellular, and optical recording studies have demonstrated that these sprouted MFs are functional, i.e., activation of these collaterals elicits excitatory responses in the dentate gyrus (21,(23)(24)(25). However, some degree of disinhibition appears necessary for pathological (epileptic) activity to be manifest in the dentate gyrus of slices prepared from sprouted, epileptic animals (24,26), suggesting that normal or augmented inhibitory responses may keep the function of these aberrant collaterals in check under normal conditions.…”
Section: Mossy Fiber Sproutingmentioning
confidence: 99%